Quick and Easy Assembly of a One-Step qRT-PCR Kit for COVID-19 Diagnostics Using In-House Enzymes - Takahashi, Masateru; Tehseen, Muhammad; Salunke, Rahul; Takahashi, Etsuko; Mfarrej, Sara; Sobhy, Mohamed A; Alhamlan, Fatimah S; Hala, Sharif; Ramos-Mandujano, Gerardo; Al-Qahtani, Ahmed A; Alofi, Fadwa S; Alsomali, Afrah; et al. (ACS Omega, 2021)
One-step reverse-transcription quantitative polymerase chain reaction (qRT-PCR) is the most widely applied method for COVID-19 diagnostics. Notwithstanding the facts that one-step qRT-PCR is well suited for the diagnosis of COVID-19 and that there are many commercially available one-step qRT-PCR kits in the market, their high cost and unavailability due to airport closures and shipment restriction became a major bottleneck that had driven the desire to produce the key components of such kits locally. Here, we provide a simple, economical, and powerful one-step qRT-PCR kit based on patent-free, specifically tailored versions of Moloney murine leukemia virus reverse transcriptase and Thermus aquaticus DNA polymerase and termed R3T (Rapid Research Response Team) one-step qRT-PCR. We also demonstrate the robustness of our enzyme production strategies and provide the optimal reaction conditions for their efficient augmentation in a one-step approach. Our kit was routinely able to reliably detect as low as 10 copies of the synthetic RNAs of SARS-CoV-2. More importantly, our kit successfully detected COVID-19 in clinical samples of broad viral titers with similar reliability and selectivity to that of the Invitrogen SuperScript III Platinum One-step qRT-PCR and TaqPath one-step RT-qPCR kits. Overall, our kit has shown robust performance in both laboratory settings and the Saudi Ministry of Health-approved testing facility.